Pengaruh Likuiditas, Aktivitas dan Kebijakan Dividen terhadap Kinerja Keuangan pada Industri Sub Sektor Telekomunikasi di Bursa Efek Indonesia - Zaudra Afifah Nurzaeni; Gendro Wiyono; Ratih Kusumawardhani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The purpose of this observe is to analyze the effect of activity, liquidity, and dividend policy on the financial performance of telecommunications companies listed on the Indonesia Stock Exchange (IDX) in the 2011-2020 period. The research method used in this research is purposive sampling method. The hypothesis test of this study uses t and F tests. The results of this study indicate that the activity ratio (CR) has a positive and significant effect on financial performance (ROA) with a regression coefficient value of 2.153 and a significance value of 0.038 <0.05. While the liquidity ratio (TATO) and dividend policy (DPR) have a positive and insignificant effect on financial performance (ROA) with a regression coefficient value of 0.019 and a significance value of 0.0849 > 0.05. Dividend policy (DPR) has a positive and insignificant effect on financial performance (ROA) with a regression coefficient value of 0.059 and a significance value of 0.557 > 0.05. Keywords: Activity (CR), Liquidity (TATO), Dividend Policy (DPR), Financial Performance (ROA).